Penerapan Irigasi Defisit pada Produksi Melon Sultan - Muhammad Idrus; I Gde Darmaputra; dian pratiwi (Journal of Horticulture Production Technology, 2026)
Deficit irrigation is the application of water to crops in amounts lower than their full water requirement without causing a significant reduction in yield. This study was conducted to investigate the effect of deficit irrigation on Sultan melon plants using a randomized block design with four levels of deficit irrigation applied from planting to harvest: 0% deficit irrigation (control), 15%, 30%, and 45%. Each treatment was replicated three times, with each replication consisting of three experimental units. The results showed that deficit irrigation had no significant effect on the number of leaves and plant height of Sultan melon, but it significantly affected leaf area, fresh stem weight, and fruit weight. The average fruit weight of Sultan melon under 0% deficit irrigation was 0.785 kg per plant, which was not significantly different from 15% deficit irrigation at 0.680 kg per plant. The deficit irrigation level that provided optimal yield and water productivity for Sultan melon was 15%, with fruit weight and water productivity of 0.704 kg per plant and 15 kg per m³ of water, respectively.